2013
DOI: 10.1097/acm.0b013e3182772b94
|View full text |Cite
|
Sign up to set email alerts
|

Policies, Activities, and Structures Supporting Research Mentoring

Abstract: Purpose To document the frequency of policies and activities in support of mentoring practices at institutions receiving a U.S. National Institutes of Health’s Clinical and Translational Science Award (CTSA). Method The study consisted of a 69-item survey with questions about the inclusion (formal or informal) of policies, programs/activities and structures supporting mentoring within CTSA-sponsored research (i.e., KL2 programs) and, more broadly, in the CTSA’s home institution. The survey, conducted from No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…Several examples are presented by infrastructure awards from NIH that support translational and multidisciplinary researchers, in HIV and other disciplines. The Clinical Translational Science Award (CTSA) (18) has successfully demonstrated the ability of these capacity building initiatives to enhance translational research efforts in multiple fields and build competencies. Similar but specific to HIV, the Centers for AIDS Research (CFAR) program has enabled both discipline specific efforts within cores as well as cross-cutting initiatives to support development of HIV researchers and HIV research infrastructure (21).…”
Section: Developing Multidisciplinary Research Teamsmentioning
confidence: 99%
“…Several examples are presented by infrastructure awards from NIH that support translational and multidisciplinary researchers, in HIV and other disciplines. The Clinical Translational Science Award (CTSA) (18) has successfully demonstrated the ability of these capacity building initiatives to enhance translational research efforts in multiple fields and build competencies. Similar but specific to HIV, the Centers for AIDS Research (CFAR) program has enabled both discipline specific efforts within cores as well as cross-cutting initiatives to support development of HIV researchers and HIV research infrastructure (21).…”
Section: Developing Multidisciplinary Research Teamsmentioning
confidence: 99%
“…9,10,11,12,13 For instance, Keyser et al, highlight the “top-down” approach to instilling effective mentorship practices at AHCs, by outlining key mentoring domains (such as fostering strong mentor-mentee relations, and optimizing the qualification of mentors) that may be strengthened through policies and activities at the institutional level, or by administrative bodies such as KL2 programs. 9 One way in which these mentorship domains may be developed and/or strengthened is via the implementation of mentor training systems.…”
Section: Introductionmentioning
confidence: 99%
“…According to the FFES, men reported being more neutral on the importance of formal mentorship and disagreed more often that it was important. A recent survey 17 of academic health centers with clinical translational science awards showed that there was considerable variability in mentorship programs across institutions, including mentor criteria, mentor-mentee relationship, incentives, and evaluative mechanisms. There are only a few published reports with quantitative outcomes measuring mentoring programs; those studies demonstrate the value of these programs.…”
Section: Commentmentioning
confidence: 99%